2021
DOI: 10.3390/jof7060407
|View full text |Cite
|
Sign up to set email alerts
|

Radionuclide Imaging of Fungal Infections and Correlation with the Host Defense Response

Abstract: The human response to invading fungi includes a series of events that detect, kill, or clear the fungi. If the metabolic host response is unable to eliminate the fungi, an infection ensues. Some of the host response’s metabolic events to fungi can be imaged with molecules labelled with radionuclides. Several important clinical applications have been found with radiolabelled biomolecules of inflammation. 18F-fluorodeoxyglucose is the tracer that has been most widely investigated in the host defence of fungi. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 97 publications
0
10
0
Order By: Relevance
“…IFD frequently occurs in critically ill and immunocompromised patients, and the symptoms may be confounded by the patient's state. 31,32 The lung is the most common portal of entry of fungi into the human body. Inhaled fungal spores or mycelia are not efficiently eliminated by the immune system of patients with immunosuppression.…”
Section: Clinical Manifestation Of Ifd In the Immunocompromisedmentioning
confidence: 99%
“…IFD frequently occurs in critically ill and immunocompromised patients, and the symptoms may be confounded by the patient's state. 31,32 The lung is the most common portal of entry of fungi into the human body. Inhaled fungal spores or mycelia are not efficiently eliminated by the immune system of patients with immunosuppression.…”
Section: Clinical Manifestation Of Ifd In the Immunocompromisedmentioning
confidence: 99%
“…In recent times, larger studies have reported the diagnostic utility of [ 18 F]FDG PET/CT in the initial evaluation and treatment response assessments of immunocompromised hosts with proven, probable, or possible IFD [26,91]. A recent study by Ankrah et al has provided insights into the relative lesion detection rates of [ 18 F]FDG PET/CT versus morphologic imaging with X-ray, CT, MRI, or ultrasound [92].…”
Section: Targeting Host Immune Responsementioning
confidence: 99%
“…In addition to radiolabeled anti-fungal drugs targeting specific molecular structures of the fungi, other non-specific antimicrobial peptides have been explored for their possible application as noninvasive probes for IFD imaging [26,141]. Ubiquicidine 29-41 (UBI 29-41) radiolabeled with 99m Tc for SPECT or 68 Ga for PET imaging have been extensively used for pyogenic skeletal and soft tissue infections [142][143][144].…”
Section: Non-specific Antimicrobial Peptidesmentioning
confidence: 99%
See 1 more Smart Citation
“…A review by Ankrah at al. provides an overview of radionuclide imaging as an adjunct for diagnosis, as well as staging of dissemination and response to treatment in fungal infections, and includes a discussion of tracers at the preclinical stage [22]. Finally, a review of strategies to augment host defense through immunomodulatory approaches has been provided by Karavalakis and colleagues, with a focus on T-cell immunotherapy against invasive fungal disease in severely immunocompromised patients [23].…”
mentioning
confidence: 99%